To solve the equation -x/2/9 = -3, we need to simplify the expression on the left side and isolate x.
First, let's clarify the expression by using parentheses correctly: (-x/2)/9 = -3.
Now, we can solve the equation step by step:
1. Multiply both sides of the equation by 9 to eliminate the denominator: 9 * (-x/2)/9 = 9 * -3
Simplifying, we have: -x/2 = -27
2. To remove the fraction, multiply both sides of the equation by 2: 2 * (-x/2) = 2 * -27
This simplifies to: -x = -54
3. Finally, to solve for x, multiply both sides of the equation by -1: (-1)(-x) = (-1)(-54)
This leaves us with: x = 54
Therefore, the solution to the equation -x/2/9 = -3 is x = 54.
What is the solution for the equation - x/2/9 = -3
1 answer